Justice, Truth, and Legal Rationality: A Leibnizian Perspective on Modern Jurisprudence - Charles Berebon (Law and Social Justice in Society, 2026)
This essay examines the relevance of Leibniz's philosophy of law for modern jurisprudence, emphasising his contributions to legal reasoning, justice, and truth. Leibniz's distinction between necessary and contingent truths, his theory of legal proof, and his multi-level approach to law—integrating strict law, equity, and morality—offer valuable insights into contemporary legal thought. His vision of a characteristic universalis, a logical system for structuring legal reasoning, anticipates modern formal methods in law. A comparison with Ronald Dworkin's legal philosophy highlights their shared commitment to objective legal principles and the integration of morality into law. While Leibniz employs formal logic and conceptual analysis, Dworkin's approach focuses on interpretive reasoning. By bridging these perspectives, this essay argues for synthesising analytical jurisprudence and natural law, demonstrating how Leibniz's ideas can help unify legal reasoning across different legal traditions and contribute to the pursuit of justice.